Statistical testing of symmetric cryptographic transformation-making - Скопа, Олександр Олександрович (Eastern-European Journal of Enterprise Technologies, 2011)
The analysis of development status of tools is conducted for testing of outputs sequences of symmetric coding devices and generators the psevdocasual sequences applied in cryptography